Linguistics materials, Frank G. Speck Papers - Boas, Franz, 1858-1942; Hallowell, A. Irving (Alfred Irving), 1892-1974; Sapir, Edward, 1884-1939 (1911)
Materials relating to linguistics. Includes an undated 4-page list of 34 questions on culturally patterned aspects of language attributed to Hallowell; correspondence with Boas relating to the American Council of Learned Societies Committee on Research in American Native Languages, principally consisting of reports on grants and their progress (1927-1934); and two folders containing 30 letters from Sapir (1911-1924). The Sapir letters cover a range of topics including Northeast material-culture specimens;s of Speck;s of Sapir; linguistic field work among the Montagnais [Innu], Cree, Delaware, Seneca, Mohawk, and Penobscot; relation of Algonquian and Wiyot-Yurok; on Yana (with Ishi); Arapaho-Cheyenne; Sapir's paper on Levirate marriage; Yurok kinship; a scheme to test response of anthropologists to an Indian design; work on his grammar of Paiute; reduction of language stocks to 6 (1920); his work on Subtiaba; relationships in and around Hokan-Coahuiltecan, and some discussion of migrations, seeing Athabaskan as late arrival. Discussion of colleagues: Mechling, Barbeau, Heye, Radin, Dixon, Skinner, Goldenweiser, Gifford, Frachtenberg, Reichard, Goddard, Boas, Hawkes.